Perception of women towards family values and their marital satisfaction. - Edalati, Ali; Redzuan, Ma’rof (Marsland Press, 2010)
The purpose of the current study is to examine the relationship between perceptions of women toward Iranian traditional values and their marital satisfaction. The 337 of women were selected as the population of the study. Stratified random sampling was used to select samples. The Kansas Marital Satisfaction (KMS) is used to measure marital satisfaction. It shows a positive relationship between perception of women toward traditional values (inequality in family affairs and inequality in regulation) and marital satisfaction. It has also shown that there is no relationship between perception of women toward traditional values of inequality in access job and inequality in political in relation to marital satisfaction. The multivariate regression analysis is utilized to answer the last objective. The analysis showed that among the two predictor variables, the variable of inequality in affairs was found to be significant in explaining the observed variation in marital satisfaction (DV). Generally, the final model has explained 4.6% of total observed variance in marital satisfaction. The findings show one reflection of the inequality and discrimination that there is in family affairs and inequality in regulation between men and women in the Iranian society. The findings highlight the need for screening and identification of other factors and unequal situations in the family and society in which women are growing.